Analisa Effectiveness Dan Oil Losses Pada Mesin Screw Press Serta Implementasi Kaizen (Continues Improvement) Untuk Peningkatan Proses Produksi Di PTPN V Sei Garo - Heri Saputra; Anita Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study aims to analyze the production process in press station using the method of Overall Equipment Effectiveness (OEE) and oil losses analysis in PTPN V Sei Garo. The OEE is a method to measure avaibility, performance, and quality of a machine. Furthermore, this research conducted the Kaizen method (continues improvement) to analyses the activities that have no value added and activities need to be improved during the production process. The result showed the OEE value of four screw press machines below the world class standard of OEE (85%). The low value of OEE was due to the availability of raw materials, so the machine was more stands by for raw materials to be processed. Oil losses of screw press machines during the monthly average of 4.67% in March, 4.74% in April, 5.645% in May, 5.86% in June, 5.744 in July and 5.26% in August. This value was still accepted by the company standard (maximum of 7%). To increase the value of OEE and decrease the value of oil losses on screw press machines should be applied Total Productive Maintenance (TPM) and Kaizen (Continues Improvement).Keywords: OEE, Six Big Losses, Oil Losses, Kaizen, Screw Press